Implementing Human Rights in the Pacific through National Human Rights Institutions: The Experience of Fiji - Byrnes, Andrew; Durbach, Andrea; Renshaw, Catherine (Victoria University of Wellington Law Review, 2009)
This article discusses the experience of the Fijian Human Rights Commission as an illustration of some of the challenges Pacific nations may face in achieving an independent and effective human rights institution in a complex and sometimes volatile socio-political context. The article argues that the presence of a supportive regional network of national human rights institutions is essential to creating and maintaining independent and effective national institutions.